The count of monte cristo - Dumas, Alexandre, 1802-1870 (Boston, Mass : Thomson Heinle, 2007)
Sent to prison an a false accusation in 1515, Edmand Dantes escapes many years later and finds a treasure which he uses to exact his revenge
Title from title screen
Keywords: French literature; Revenge -- Fiction; Adventure and adventurer -- Fiction; France -- Social life and customs -- 19th century -- Fiction